Integrating Powtoon Animation as a Digital Innovation for Enhancing Elementary Students’ Mathematical Conceptual Understanding - Intan Andriani Hasanah; Lutfiah Isfa Hayati; Siti Zaina; Raudhatunnur Raudhatunnur; Dwi Novita Sari (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mathematics instruction in elementary schools often presents challenges due to the abstract nature of concepts, especially in geometry. Digital innovations like animated media offer potential to enhance students' conceptual understanding and engagement. This qualitative case study explored the integration of Powtoon animation in teaching three-dimensional geometry to fifth-grade students at Palembang Integrated Islamic Elementary School. Data were collected through classroom observations, semi-structured interviews with teachers and administrators, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, involving data reduction, display, and conclusion drawing. Findings reveal that Powtoon enhanced students’ conceptual understanding by providing dynamic visualizations, contextual illustrations, and simplified representations of complex ideas. The media supported student activeness, creativity, analytical thinking, and innovation. Teachers used Powtoon to deliver content in both structured and collaborative formats, tailored to classroom needs. Institutional factors—including principal leadership, infrastructure readiness, and teacher training—played a crucial role in supporting successful implementation. The study highlights the effectiveness of Powtoon in addressing pedagogical challenges in elementary mathematics. Its integration fosters student-centered learning and aligns with constructivist and multimedia learning theories. Positive student responses indicate increased motivation, participation, and cognitive engagement. The study also emphasizes the importance of school-wide support in sustaining digital innovations. Powtoon is a feasible and effective tool for improving mathematical conceptual understanding at the primary level. Future research should explore its broader application across diverse educational settings to validate these findings.